MENINGKATKAN KOMPETENSI DIGITAL PELAKU USAHA STUDIO: IMPLEMENTASI SISTEM RESERVASI ONLINE MELALUI WEBSITE INTERAKTIF - Koko Setianto; Taufiqurrohman; Rika; Sifa Paujia; Hanifah (PEMTEKDIKMAS (PENGABDIAN EKONOMI MULTIDISIPLIN TEKNOLOGI PENDIDIKAN UNTUK MASYARAKAT), 2024)
Digital competency development for small business entrepreneurs is critical capability gap limiting UMKM effectiveness in digital economy. While previous PKM initiatives successfully implemented web-based reservation systems, sustaining technology adoption requires ongoing competency development, user interface optimization, and business process alignment. This Community Service Program (PKM) advanced Kilas Graduation digital transformation through comprehensive digital competency building combined with enhanced website interface redesign. Program involved: (1) digital skills assessment and competency gap analysis; (2) interactive website interface redesign prioritizing user experience; (3) comprehensive digital competency training covering business process optimization; and (4) continuous support for sustained technology adoption. Enhanced interface improvements include: streamlined booking workflow, mobile-responsive design, intuitive navigation, real-time dashboard analytics, and customer communication tools. Participants: 1 owner and 4 staff members. Results after 5 weeks demonstrated: booking completion rate improved 28%, user interface satisfaction increased to 8.9/10, staff digital competency score improved from 6.2 to 8.1/10, system adoption consistency maintained at 72%, and business process efficiency improved 23%. Training satisfaction achieved 91% with 96% competency achievement.